2021
DOI: 10.1101/2021.11.30.470682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ligand-induced changes in dynamics mediate long-range allostery in thelacrepressor

Abstract: Allostery, broadly defined as a protein’s functional response to distal perturbations, is fundamental to biological regulation. In classical models, allosteric ligand binding produces a defined set of structural changes in the protein, resulting in a different low-energy conformation. Proteins that undergo ligand-induced allostery with few observable structural changes therefore frustrate interpretations by classical models. Here we used hydrogen-deuterium exchange with mass spectrometry (HDX/MS) to map the al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Previous studies have identified motions related to DNA-binding specificity in EcLacI occur over ns -μs timescales, consistent with the timescale of our simulations. 48,49 We observe asymmetry in the protein-DNA interactions between the two monomers that constitute the functional dimer (Fig. 5d,e).…”
Section: Many Of These Residuesmentioning
confidence: 90%
“…Previous studies have identified motions related to DNA-binding specificity in EcLacI occur over ns -μs timescales, consistent with the timescale of our simulations. 48,49 We observe asymmetry in the protein-DNA interactions between the two monomers that constitute the functional dimer (Fig. 5d,e).…”
Section: Many Of These Residuesmentioning
confidence: 90%